Trends in hospitalizations from all-cause gastroenteritis in children younger than 5 years of age in Brazil before and after human rotavirus vaccine introduction, 1998 - 2007 - Lanzieri, Tatiana Miranda (2010)
Rotavirus vaccination was introduced in Brazil in March 2006.We describe trends in hospitalizations from all-cause gastroenteritis in children younger than 5 years during pre- and postvaccination periods using hospital discharge data from Brazil Hospital Information System (SIH-SUS). A reduction in gastroenteritis hospitalizations of 26% and 48% in 2006 and in 2007, respectively, was observed among children younger than 1 year compared with prevaccination period (1998 2005). The largest reduction rates among children younger than 1 year were noted in the South and Southeast regions, approximately 56% in 2007, where vaccine coverage was the highest.